Correction: Severe cases of seasonal influenza in Russia in 2017-2018. - Natalia P Kolosova; Tatyana N Ilyicheva; Alexey V Danilenko; Julia A Bulanovich; Svetlana V Svyatchenko; Alexander G Durymanov; Natalia I Goncharova; Andrei S Gudymo; Alexander N Shvalov; Ivan M Susloparov; Vasiliy Y Marchenko; Tatyana V Tregubchak; et al. (PLoS ONE, 2019)
[This corrects the article DOI: 10.1371/journal.pone.0220401.].